WORLD EXPERIENCE OF BALANCED USE OF LAND-RESOURCE POTENTIAL IN THE AGRARIAN SECTOR - Сидорук, Б. О. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
There is a tendency to deterioration of soil quality today: reduction of humus; increasing its acidity; deteriorating balance of nutrients in the soil and so on. Therefore; the balance of land use is one of the necessary conditions for improving the quality of agricultural land and addressing the problems of rational use of land-resource potential. Research was conducted by use of the dialectical method of knowledge of the economic laws and the systematic approach to the study of economic phenomena; monographic; abstraction; abstract and logical method. The article investigates the world experience of balanced use of agricultural land. The features of alternative agricultural systems and their influence on qualitative indicators and reproduction of land-resource potential are highlighted. Agricultural systems are being systematized; which are used in modern agricultural production in the direction of ensuring of balanced agrarian land use. It has been established that further research should be aimed at exploring the possibilities of using the world experience of balanced land use for the development of integrated programs in order to stimulate those areas of agrarian activity that are developing internationally and provide consumer needs of the population; protection and restoration of the natural environment.